Inflammatory Myopathy in Horses With Chronic Piroplasmosis. Issue 1 (January 2018) - Pasolini, Maria P.; Pagano, Teresa B.; Costagliola, Alessandro; Biase, Davide De; Lamagna, Barbara; Auletta, Luigi; Fatone, Gerardo; Greco, Michele; Coluccia, Pierpaolo; Veneziano, Veneziano; Pirozzi, Claudio; Raso, Giuseppina Mattace; et al.
Horses affected by chronic piroplasmosis may develop poor performance and muscle atrophy. Here we investigate the pathological and immunopathological aspects of myopathy occurring in chronic equine piroplasmosis. The study included 16 horses serologically positive for equine piroplasms presenting with clinical signs and supporting serum biochemical evidence of a myopathy. Skeletal muscle was evaluated by histopathology, immunohistochemistry, indirect immunofluorescence, and molecular detection of piroplasms and inflammatory cytokines in skeletal muscle. Histologic lesions included muscle fiber atrophy (100% of cases), degenerative changes (13/16, 81%), and perivascular perimysial and endomysial lymphocytic infiltrates (81% of cases). In 15 cases (94%), muscle fibers had strong immunostaining for major histocompatibility complex classes I and II. T lymphocyte populations were mainly CD3+, CD8+, and CD4+ in equal proportions, with a lower number of CD79α+ cells. The serum from affected horses was tested by indirect immunofluorescence for binding of IgG, IgM, or IgA to sections of normal equine muscle to detect circulating autoantibodies against muscle antigen(s). In all cases, distinct sarcolemmal staining was detected in sections incubated with serum from affected horses, in contrast to sections incubated with phosphate-buffered saline or equine control sera. Reverse transcription polymerase chain reaction (RT-PCR) testing of muscles from affected animals revealed a significant increase of interferon-γ, interleukin-12, and tumor necrosis factor–α gene expression compared to healthy controls. Theileria equi or Babesia caballi was not detected in samples of affected muscle by RT-PCR. Thus, inflammatory myopathy associated with equine piroplasmosis may involve an autoimmune pathogenesis with upregulation of inflammatory cytokines that may cause myofiber atrophy and degeneration.